2018
DOI: 10.1021/acs.langmuir.8b03107
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Inorganic Hybrid Thin Films Fabricated by Layer-by-Layer Assembly of the Phosphorylated Cellulose Nanocrystal and Imogolite Nanotubes

Abstract: Phosphorylated cellulose nanocrystal (P-CNC)/imogolite nanotube (natural aluminosilicate nanotube) hybrid thin films were fabricated by spin-assisted layer-by-layer assembly. Phosphorylation of CNC with diammonium hydrogen phosphate ((NH4)2HPO4) was carried out to introduce phosphate groups on the CNC surface for enhanced interaction with imogolite. Structure of the P-CNC/imogolite thin film was characterized by atomic force microscopy, scanning electron microscopy, X-ray diffraction (XRD), and grazing inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 54 publications
(101 reference statements)
1
20
1
Order By: Relevance
“…Excess amounts of urea were used to prevent the degradation of cellulose caused by the released phosphoric acid at an elevated temperature. [213,214] Phosphorylation usually takes place in the presence of organic solvents, such as N,N-dimethylformamide (DMF), pyridine, or urea, which are used to swell cellulose fibers to increase the homogeneity of the phosphorylation reaction. Introduced amounts of phosphate groups heavily depend on the amounts of the phosphorylating agents, reaction time and temperature.…”
Section: Negatively Charged Nanocellulosementioning
confidence: 99%
“…Excess amounts of urea were used to prevent the degradation of cellulose caused by the released phosphoric acid at an elevated temperature. [213,214] Phosphorylation usually takes place in the presence of organic solvents, such as N,N-dimethylformamide (DMF), pyridine, or urea, which are used to swell cellulose fibers to increase the homogeneity of the phosphorylation reaction. Introduced amounts of phosphate groups heavily depend on the amounts of the phosphorylating agents, reaction time and temperature.…”
Section: Negatively Charged Nanocellulosementioning
confidence: 99%
“…The thickness of each bilayer is ∼10 nm, slightly larger than that of dip-assisted LBL assembly of polyelectrolyte/imogolite films (which is around several nanometers 23,24 ) and also much larger than the 2 nm thickness of each CNC/imogolite bilayer. 25 This is because, compared with the sparsely surface charged CNC, 34 the densely surface charged sacran has a strong electrostatic attraction with the imogolite, resulting in a larger bilayer thickness. For another tubular clay, halloysite nanotube, in the LBL assembly process, each bilayer thickness of halloysite/ poly(ethylenimine) is about 54 nm, 35 much larger than the sacran/imogolite bilayer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…23,24 For instance, our very recent work demonstrated that imogolite can be employed in the fabrication of LBL films with CNC. 25 However, because of the weak electrostatic attractions and rigidities of both CNC and imogolite, the resulting hybrid film was found to be unstable under harsh conditions, such as acidic solution, and appeared very brittle when peeled from a substrate. Nonetheless, because of the flexible structure, presence of many functional groups, large molecular weight, and the high surface charge of sacran, a free-standing sacran/ imogolite film can be fabricated owing to the strong interaction between imogolite and sacran.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, different types of functional materials based on clay minerals have been also prepared; pillared clays and polymer–clay nanocomposites are the best-known examples [7]. Besides classical layered silicates, clays showing other morphologies, such as fibrous (sepiolite and palygorskite) and tubular (halloysite and imogolite) clays, could also be interesting nanoparticulated solids in this context [811]. Sepiolite (SEP) and palygorskite are attracting increasing attention in the development of nanoarchitectured materials in applications such as catalysis or biomedicine [8].…”
Section: Introductionmentioning
confidence: 99%